Ecologías cuir with Gloria Anzaldúa: Systematization of an Investigative Experience where Plants resist Cement in Southern Chile - Puppo Stuardo, Alfo (2026)
This article systematizes a research experience conducted in neighborhoods located in southern Chile, where plants emerge as relational agents mediating affects, memories, and territorial disputes. Through co-production of narratives, 4 stories were developed that reveal everyday ties with urban nature and the tensions imposed by neoliberal urbanization. Drawing from cuir theoretical frameworks, the study interprets psychic and collective fragmentations that foster practices of repair, plant-based care, and the recomposition of the body-territory. Additionally, a curatorial photomontage is created, articulating the embodied reflexivity of my research process. The article contributes by offering creative and situated methodologies that destabilize hegemonic modes of articulating and producing context-anchored knowledge, making visible mestizo memories, colonial wounds, and multispecies alliances as foundations for imagining cuir ecologies rooted in territory.